A Dynamic Model of Investor Decision-Making: How Adaptation to Losses affects Future Selling Decisions - Carmen Lee; Roman Kraeussl; André Lucas; Leonard J. Paas (Tinbergen Institute, 2008)
We conduct an experiment to test whether the size of a loss and the time in a losing position affect investors' adaptation to the loss situation and, subsequently, whether this adaptation affects future investment decisions. As investors adapt to losses, their neutral reference point shifts downwards causing losses to become psychologically less painful. This shift in reference point is a dynamic process that is updated every time new information is received about the stock's performance. The dynamically changing reference point, together with changing perceptions on the stock's expected future performance, together influence the decision to hold on to or to capitulate on an investment. We study the relative contribution of each of these components as well as their inter-relationships in a dynamic experimental design. Our results indicated that a larger loss size and a longer time in a losing position are related to higher adaptation levels. These higher adaptation levels relate to less positive emotions and less optimistic expectations about future price changes. The actual decision to capitulate an investment, however, only depends directly on the expectation about the stock's future performance. The adaptation level, by contrast, affects the actual investment decision indirectly via its impact on expectations.
Keywords: C91; D03; D81; 330; adaptation; capitulation; selling decisions; investment; Anlageverhalten; Entscheidung bei Risiko; Prospect Theory